High intensity exercise affects diurnal variation of some biological markers in trained subjects - Hammouda, O.; Chtourou, H.; Chahed, H.; Ferchichi, S.; Chaouachi, A.; Kallel, C.; Miled, A.; Chamari, K.; Souissi, N. (International Journal of Sports Medicine, 2012)
The study investigated if markers of muscle injury and antioxidant status were affected by a Wingate test performed at 2 different times of day. 15 young male footballers performed 2 tests (randomized) at 07:00-h and 17:00-h. Fasting blood samples were collected before and 3 min after each test for assessment of markers of muscle injury and antioxidant status. Resting oral temperature was recorded during each session. Peak power (10.76±1.05 vs. 11.15±0.83 W.kg - 1) and fatigue index (0.41±0.04 vs. 0.49±0.13%) during the Wingate test, and core temperature, were significantly higher (all p<0.05) in the evening. Markers of muscle injury were significantly higher in the evening before and after exercise (e. g., 148.7±67.05 vs. 195±74.6 and 191.6±79.52 vs. 263.6±96.06 IU.L - 1, respectively, for creatine kinase; both p<0.001). Antioxidant parameters increased after the Wingate test but only resting values were significantly higher in the morning (e. g., 1.33±0.19 vs. 1.19±0.14 µmol.L - 1 for total antioxidant status; p<0.05). The results indicate that muscle injury and antioxidant activity after the Wingate test were higher in the evening, suggesting a possible link between the biochemical measures and the diurnal fluctuation of anaerobic performance. However, repetition of this study after prescribed rather than self-selected exercise intensity is recommended.